Livogrit mitigates ANIT-induced cholestasis-like symptoms in an in vivo model by curbing hepatic inflammation and regulating BAX, TGF-β, MMP-9 and α-SMA gene expression - Acharya Balkrishna; Ritu Paliwal; Surjeet Singh; Rani Singh; Vivek Gohel; Rishabh Dev; Kunal Bhattacharya; Sandeep Sinha; Anurag Varshney (Heliyon)
Bile duct constriction disrupts bile acid flow causing cholestasis, hepatic necrosis, fibrosis, and cirrhosis. The study investigated hepatoprotective effectiveness of Ayurvedic prescription herbal medicine “Livogrit” commercially available in India, against α-naphtylisothiocyanate (ANIT)-induced cholestasis-like symptoms in male Sprague-Dawley rats. Livogrits's phytochemical profiling showed the presence of Gallic acid, Methyl Gallate, Catechin, Corilagin, Ellagic acid, Rutin, and Cinnamic acid. Sprague-Dawley rats were pre-treated with Livogrit (20–600 mg/kg/day) and reference drug Ursodeoxycholic acid (100 mg/kg/day) for 15 and 5 days, respectively, before single-dose ANIT (100 mg/kg) stimulation. Livogrit treatment protect the rats against ANIT-induced increase in blood serum markers (total bile acids, ALT, AST, GGT, ALP, total cholesterol, and total bilirubin) and reduced manifestation of liver necrosis, inflammation, and periportal fibrosis. At molecular level, Livogrit inhibited up-regulation of BAX, TGF-β, α-SMA, and MMP-9 mRNA expressions, associated with the liver damages. Taken together, this study supported Livogrit's potential as hepatoprotective medicine against cholestasis-like-etiologies.